2016
DOI: 10.2196/mhealth.6540
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effectiveness of Using Wearable Activity Trackers in Youth: A Systematic Review

Abstract: BackgroundThe proliferation and popularity of wearable activity trackers (eg, Fitbit, Jawbone, Misfit) may present an opportunity to integrate such technology into physical activity interventions. While several systematic reviews have reported intervention effects of using wearable activity trackers on adults’ physical activity levels, none to date have focused specifically on children and adolescents.ObjectiveThe aim of this review was to examine the effectiveness of wearable activity trackers as a tool for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
223
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(241 citation statements)
references
References 33 publications
(77 reference statements)
5
223
1
2
Order By: Relevance
“…Furthermore, following the 8-week period, significant increases in amotivation were observed. In contrast to previous literature suggesting that healthy lifestyle technologies can impact young people's motivation for physical activity, [24][25][26] data demonstrate that healthy lifestyle technologies may impact negatively on students' motivation for physical activity. In examining the relationship between the Fitbit and young people in further detail, data suggested that peer comparison was a key factor in undermining levels of competence, autonomy, and relatedness.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, following the 8-week period, significant increases in amotivation were observed. In contrast to previous literature suggesting that healthy lifestyle technologies can impact young people's motivation for physical activity, [24][25][26] data demonstrate that healthy lifestyle technologies may impact negatively on students' motivation for physical activity. In examining the relationship between the Fitbit and young people in further detail, data suggested that peer comparison was a key factor in undermining levels of competence, autonomy, and relatedness.…”
Section: Discussioncontrasting
confidence: 99%
“…23 Young people (age [11][12] have also reported finding features of real-time feedback and competition from the commercial Fitbit motivating, 24 suggesting that promotion of self-monitoring and goal-setting behaviors can increase physical activity levels. 25,26 Yet the evidence base on the health-related impact of young people's (age [13][14] use of healthy lifestyle technologies is limited. 14,20,21 A recent systematic literature review on adolescents and young adults (age 12-25 years) identified only 2 empirical studies that measured the health-related effects of using nutritional or physical activity apps.…”
Section: Introductionmentioning
confidence: 99%
“…Prior feasibility studies with GPS devices for location-tracking in health have surfaced similar issues in use of such devices [31,44]. Moreover, previous work shows that GPS devices typically only function outdoors, where they can connect with multiple satellites, and perform best in places away from dense buildings [10,11].…”
Section: Comparisons With Prior Workmentioning
confidence: 94%
“…To date, a variety of pilot and feasibility studies have examined user acceptance of devices such as wearable activity trackers [9,10], dedicated GPS devices [11], and GPS-enabled smartphones [12,13]. While this research generally shows reasonable acceptance among varied user groups, there remain gaps in understanding the spatial accuracy of each of these devices -particularly those that are available on the consumer market and thus could facilitate population-level research.…”
Section: Introductionmentioning
confidence: 99%
“…This stream of research suggests that activity tracking devices, by offering mechanisms such as goals reinforcement, gamification, and possibilities for social competition generate greater awareness about one's activity, and motivate engagement in specific fitness-related activities and behaviors [5,8,9]. Several studies in the past three years [e.g., 6,7,10,11] have focused on how different groups of users perceive and interact with the affordances of activity tracking devices.…”
Section: Related Researchmentioning
confidence: 99%